Inpatient Perioperative Formulary Restriction of Intravenous Acetaminophen at Vizient Partner Hospitals: A National Survey of Pharmacists. (December 2021) - Wallskog, Kirsten Elena; Lauderdale, Stacy; Peppard, William J.; Kirkwood, Craig; Taylor, Stacy; Johnston, Susan
Purpose: Despite potential benefits of intravenous (i.v.) administration of acetaminophen (APAP), consistent outcome data are lacking. This, combined with the higher acquisition cost of the drug, has led to variation in i.v. APAP management strategies. This project evaluated the contemporary formulary status and restrictions of i.v. APAP in the perioperative setting.Methods: A survey focusing on i.v. APAP formulary restriction in the perioperative setting was developed by the Vizient Pharmacy Research Committee and distributed to Vizient Pharmacy Program participant listservs for Pharmacy Directors or Drug Information Pharmacists. The four survey domains included hospital characteristics, perioperative i.v. APAP formulary status and prescribing restrictions, perioperative i.v. APAP use, and perioperative i.v. APAP medication use evaluation (MUE) results. Responses were collected and summarized, and primary outcomes were evaluated using Fisher's exact test.Results: A total of 1195 surveys were distributed with a response rate of 19%. Respondents were equally distributed between academic medical centers (AMC) and non-academic medical centers (non-AMC). Two cohorts were examined: those with i.v. APAP on formulary and those without. The non-AMCs showed a larger proportion of hospitals with the medication on formulary ( P  = .041). Regarding formulary decision-making, the AMCs were more considerate of value. Several different practices were employed to limit or restrict i.v. APAP.Conclusion: A survey of directors of pharmacy and drug information specialists revealed that the majority of hospitals have i.v. APAP on formulary for perioperative use, but use is restricted. Differences in i.v. APAP formulary practices between AMCs and non-AMCs warrant further consideration.